A Legal Review of the “First to File” Principle in Indonesia’s Trademark Registration System - Syifa Sofia Agustin; Jasmine Azzahra; Windi Putri Oktapiani (Anthroposia: Journal of Social and Human Development, 2026)
This study examines the legal construction, application, and limitations of the First to File principle within Indonesia’s trademark registration system. The research employs a non empirical normative legal method grounded in doctrinal legal inquiry. Legal materials consist of Law Number 20 of 2016 concerning Trademarks and Geographical Indications, Government Regulation Number 22 of 2018 concerning International Trademark Registration under the Madrid Protocol, relevant ministerial regulations, international legal instruments, and scholarly literature on intellectual property law. The analysis applies statutory, conceptual, and doctrinal approaches supported by grammatical, systematic, and teleological interpretation. The findings indicate that the First to File principle functions as the central mechanism for allocating trademark rights and promoting legal certainty through a constitutive registration framework. The study also demonstrates that the principle is not absolute because its operation is constrained by doctrines concerning good faith, protection of well known marks, prior reputation, and judicial intervention in cases involving substantive injustice. The research further identifies the need for stronger substantive examination, improved institutional safeguards, enhanced protection for small business actors, and broader dispute resolution mechanisms. A balanced framework integrating legal certainty and substantive justice is essential for the future development of trademark protection in Indonesia.